Scouting Strategy in Implementation Character Building at Sekolah Alam Ungaran (SAUNG) - Retno Widiastuti; Yuli Utanto; Haryono Haryono (Universitas Negeri Semarang, 2023)
Character education is an important issue caused by the emergence of the behavior of the younger generation that is contrary to Indonesian religious, social, legal, and cultural norms. The objectives of this study are to analyze Scouting learning strategies in the implementation of Character Building in SAUNG, analyze the results of the impact of scouting on changes in student behavior in SAUNG, and analyze implementation barriers and solutions. This research uses descriptive qualitative methods. The subject of the study consisted of the Principal, teachers, and students at the Alam Ungaran School. Data analysis techniques are carried out by data collection, data reduction, data presentation, and conclusions. The validity of the data uses source triangulation and engineering triangulation. The results of this research are through the Scouting strategy in the implementation of Caracter Building in SAUNG schools which includes planning, implementing, and evaluating, which can shape student behavior discipline, leadership spirit, confidence, and responsibility. Obstacles that often occur include a lack of character building from the environment outside the school such as the community and family environment. The solution is through habituation and approach to students. The existence of this research can be a reference to form good character in students.